Fortalecimiento de la educación ambiental en el aula de matemáticas de los estudiantes de grado séptimo del Colegio Parroquial San Luis Gonzaga - Ardila Garzón, Oscar Alejandro (Universidad Antonio Nariño, 2023)
Critical mathematical education as a branch of research in mathematics education, proposes a facet of mathematics as an element of transformation of the subjects that belong to the classroom, providing as a tool solid arguments that allow students to actively participate in the transformation of their context